Palynological characterization of species of Verbenaceae J. St.-Hil. and Lamiaceae Martinov (Lamiales Bromhead) - Gabriele Patricia Vitoria da Silva; Bruna Tereza Possamai; Gabriel da Rosa Schroeder; Nilton Paulo Vieira Junior; Enderlei Dec; Denise Monique Dubet da Silva Mouga (Acta Biológica Catarinense, 2017)
Clerodendrum splendens A. Chev., Clerodendrum x speciosum Tiej. & Binn, Clerodendrum thomsonae Balf. F., Clerodendrum ugandense L., Congea tomentosa Roxb., Duranta erecta L., Petrea volubilis L. and Petrea volubilis f. albiflora (Standl.) Standl. pollen grains were acetolyzed, photographed and measured under light microscopy and scanning electron microscopy. Values presented are averages in micrometers. Grains are monads, radially symmetrical, isopolar, large (C. ugandense, very large, C. tomentosa, small-medium and D. erecta, medium),tricolpate (P. volubilis f. albiflora, dimorphic grains with 3-4 colpus). Ambitus is circular (C. tomentosa and D. erecta, sub-circular, P. volubilis , triangular, P. volubilis f. albiflora, triangular-quadrangular). The form is oblate-spheroidal (C. splendens, C. x speciosum, C. ugandense), prolate-spheroidal (C. thomsonae), prolate (C. tomentosa), suboblate (D. erecta) and oblate (P. volubilis, P. volubilis f. albiflora). Exine thickness is in C. splendens 4,28, C. x speciosum 4,19, C. ugandense 4,33, C. thomsonae 4,18, C. tomentosa 1,4, D. erecta 1,55, P. volubilis 2,49, P. volubilis f. albiflora 2,68. Ornamentation is micro-echinate (C. splendens, C. x speciosum, C. thomsonae), echinate (C. ugandense), reticulate (C. tomentosa), psilate (D. erecta, P. volubilis, P. volubulis f. albiflora). Duranta and Petrea are close to Verbenaceae pattern, Congea to Lamiaceae and Clerodendrum loosely to Lamiaceae.